Innovation Activity of Slovak SMEs Operating in the ICT Sector (Marketing i Menedžment Innovacij)
The objective of this study was to analyse contemporary trends in innovation among small and medium–sized enterprises in Slovakia's ICT sector. The study explored different types of innovations, the factors that either promote or hinder innovation, and the innovative practices of small and medium–sized enterprises within this sector. To achieve this goal, a questionnaire survey was conducted between September 2021 and February 2022. The research sample consisted of 1,000 randomly selected small and medium–sized enterprises operating in the ICT sector, drawn from a total of 8,416 eligible companies. Ultimately, 124 respondents completed the questionnaire, including 73 microenterprises and 51 small and medium–sized enterprises. The research hypotheses were evaluated via descriptive statistical analysis and the Z score methodology. The findings revealed that the most prominent form of innovation in Slovakia's ICT sector was service innovation, followed by product innovation and the adoption of new production processes. The primary motivational factor driving innovation is the desire to achieve high customer satisfaction by meeting customer needs and enhancing service quality. Conversely, the most significant barrier to innovation was identified as a lack of time. The study indicated that approximately 75% of small and medium–sized enterprises intend to pursue innovation within the next few years. Moreover, innovation plans were more pronounced among small and medium–sized enterprises than among microenterprises. The primary areas of interest for future innovations included enhancing existing products and services, developing new products or services, and implementing new technologies or production processes. With respect to the research hypotheses, no statistically significant differences were observed between the innovation activities of microenterprises and those of small and medium–sized enterprises.